A preliminary trial comparison of several anesthetic techniques in cats - Cruz, Mariângela L. [UNESP]; Luna, Stelio P.L. [UNESP]; De Castro, Gladys B. [UNESP]; Massone, Flávio [UNESP]; Rosa, André L. [UNESP] (My University, 2000)
The aim of this study was to investigate the effect of several drug combinations (atropine, xylazine, romifidine, methotrimeprazine, midazolam, or fentanyl) with ketamine for short term anesthesia in cats. Twelve cats were anesthetized 6 times by using a cross-over Latin square protocol: methotrimeprazine was combined with midazolam, ketamine, and fentanyl; midazolam and ketamine; romifidine and ketamine; and xylazine and ketamine. Atropine was combined with romifidine and ketamine, and xylazine and ketamine. Temperature, heart rate, and respiratory rate decreased in all groups. Apnea occurred in 1 cat treated with methotrimeprazine, romifidine, and ketamine, suggesting that ventilatory support may be necessary when this protocol is used. Emesis occurred in some cats treated with α2-adrenoceptor agonists, and this side effect should be considered when these drugs are used.